PERBANDINGAN PENGARUH TEKNIK PEMODELAN ENTITY-RELATIONSHIP MODEL DAN RESOURCES-EVENTS-AGENTS MODEL ATAS PERANCANGAN DATABASE PERUSAHAAN - Michael Iskandar (Bina Ekonomi, 2010)
Databases are an important part of most computer-based information systems. As such, the design of a database has also gained importance because a bad design will compromise data integrity as well as make it inefficient in its use of resources. This paper compares the effect of two data modeling approaches on the design of a database, specifically the Entity-Relationship Model (ER Model) and the Resources-Events -Agents Model (REA Model).  First, the sales/collection cycle of a fictional case study is described.  Then, an ER Model and a REA Model are independently created based on this case study. Finally, one database design is created based on the ER Model, and another database design is created based on the REA Model. The outcome of this experiment shows that both approaches produced similar database designs, but the design processes were different in their complexity, structurally, and completeness. A significant difference is that the ER Model closely followed those aspects that were already laid out by the case study, while the REA Model started out by building a most complete data model, over and above the one described in the case study.